Cellular Energetics : Thermodynamics of Cycling Between Coupled Reactions. - Diederichs, Frank (Walter de Gruyter GmbH, 2019)
This monograph describes metabolic and transport reactions of muscle cells using the laws of chemical thermodynamics. In particular, the thermodynamics of irreversible processes are used to formulate coupled reactions and their outcome on steady state cycling. The effects of ATP cycling on energy metabolism and heat production is described. The results of mathematical simulations of metabolism are used to underline theoretical approaches.- Resumé vydavatel